LEARNERS’ DIGITAL LITERACY IN THE ONLINE LEARNING DURING COVID-19 - Iful Rahmawati Mega; Yuanita Yuanita; Ayen Arsisari; Widati Amalin Ulfah (University of Kuningan, 2022)
This research investigates the understanding of digital literacy in the online learning process during covid-19 for students in the Higher Education students in Indonesia. The objectives of this study are to describe the aspects of digital literacy in the concepts of Bawden, they are basic skill of digital literacy, attitudes and perspectives, background knowledge of the information, technology and iinformation skills, and attitudes and perspectives. This study employ qualitative with the subjects are 117 students; these students were determined using purposive sampling technique with the criteria who were joining the learning classroom actively. The collecting data technique was using 20 questions in the questionnaire and it was analyzed using descriptive quantitative techniques. The results in this study reveal that all of the respondents indicate have good criteria in digital literacy. They have good characteristics in basic skill of digital literacy; have good criteria in background knowledge of the information; have good skill in technology and information; as well as good attitude and perspective of digital literacy. The conclusion is the higher education students have a good digital literacy in the aspect of basic skill of digital literacy, they have a good digital literacy in the aspect of background knowledge of information, and they have a good digital literacy in the term of technology and information skills as well as strong attitude and perspective on digital information.